Peran Persepsi Risiko Dalam Memediasi Pengaruh Literasi Keuangan dan Media Sosial Terhadap Keputusan Investasi Mahasiswa di Kota Kediri - Algifari, Annas AQ; Nadhiroh, Umi; Dewi, Anita Sumelvia; Fahrezi, Ricard Ryan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Investment decisions among university students have become increasingly important along with the rapid growth of digital investment platforms and investment-related information on social media. This study aims to examine the effect of financial literacy and social media on investment decisions through risk perception as a mediating variable among university students in Kediri City. This research used a quantitative explanatory approach. The sample consisted of 160 students who had investment experience in the capital market and were selected using purposive sampling. Data were collected through an online questionnaire using a five-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that financial literacy has a positive and significant effect on investment decisions. Social media also has a positive and significant effect on investment decisions. Financial literacy and social media have positive and significant effects on risk perception, while risk perception has a positive and significant effect on investment decisions. Furthermore, risk perception mediates the relationship between financial literacy and investment decisions, as well as the relationship between social media and investment decisions. These findings indicate that students’ investment decisions are shaped by cognitive ability, digital information exposure, and risk evaluation. The study implies that financial education and critical evaluation of social media investment content are essential for improving students’ investment decision quality.